Evaluation of the Efficiency of Public Drinking Water and Reverse Osmotic Water (RO) in Some Areas in the Province of Karbala - Wafaa S.H. Al–Nasrawi, Alyaa Neamah Najm Alsaedi, Noor Hameed Alkharsan, Naeema Hameed Aldulaimy, (Pakistan Journal of Medical & Health Sciences, 2022)
Drinking water is one of the necessary and continuous human needs that cannot be dispensed for any reason and must meet the water quality standards in terms of taste and color in addition to the physical, chemical and biological specifications, and this study came to know some characteristics of the quality of public drinking water as well as drinking drinking water RO in some areas In the city of Karbala, physical and chemical quality assessment and comparison of results with Iraqi and international standards. Where some factors were measured, such as pH, turbidity, total soluble solids, hardness, calcium, magnesium, sulfate, and nitrates, and it was observed that all traits conform to Iraqi and international standards. The results also showed that all results of public drinking water were higher than the results of drinking RO water and most of the readings with regard to RO drinking water were much less than the limits permitted internationally and Iraq.